Savings Whichare in Excess of one's Needs - FARHAT, Dr. M. L. F. FARHAT (Dirasat in Economics and Business, 1978)
The purpose of this paper is to investigate the benav„ of a society in which no consumer is all owed tr., keep the he needs. To prepore for discussion and anafresi% following model will be adopted